Semantic preference and prosody of the ‘aftermath of N’ construction: A corpus-based investigation - Wiliński, Jarosław (Papers in Linguistics, 2026)
This article examines the ‘aftermath of N’ construction using usage-based construction grammar along with concepts such as semantic preference and prosody. Based on data from the Corpus of Contemporary American English (COCA) and employing a quantitative corpus-based approach, the author identifies the discourse prosody of this construction and its semantic preference for specific categories of nouns. The study also establishes the structural, semantic, pragmatic, distributional, and discourse-functional properties of the construction while identifying the nouns most closely associated with it. The results indicate that the construction in question primarily exhibits a negative semantic prosody and a marked semantic preference for nouns denoting violent, catastrophic, or emotionally charged events. Thus, it functions as a discursive tool for reflecting on the consequences of impactful events. However, the corpus evidence also reveals that when the construction occurs with neutral or positive nouns (e.g., visit, meeting, or success), particularly in contexts where a logical order or sequence of events is more significant than an evaluative stance, its usual negative semantic prosody is weakened or neutralized. The phrase no longer evokes the negative connotations associated with disasters or crises. Rather, it fulfils the function of a temporal and causal marker, denoting simply ‘after/following’.